Involvement of second messengers in regulation of the low-density lipoprotein receptor gene. - Auwerx, J H (1989)
Transcription of the low-density lipoprotein receptor (LDL-R) gene in the human monocytic leukemic cell line THP-1 and in the human hepatocarcinoma cell line Hep-G2 is regulated by second messengers of the diacylglycerol-protein kinase C (DAG-PKC), inositol 1,4,5-triphosphate-Ca2+, and cyclic AMP pathways. Exogenous phospholipase C (which releases DAG and inositol 1,4,5-triphosphate), PKC activators (phorbol esters and DAG), Ca2+ ionophores, and a cyclic AMP analog all transiently induced accumulation of LDL-R mRNA. The effects of these three signal-transducing pathways were to a large extent additive. Furthermore, PKC stimulation effected an increase in LDL binding, which suggested that the increase in LDL-R mRNA resulted in an increase in functional cell surface receptor activity. These results suggest that uptake of cholesterol by these cells is under control of both intracellular cholesterol levels and external signals.